Nets hauled at the shore - Mumbai Archive Project Team (Jio Institute, 2024)
Upon returning, the nets are hauled to shore. Smaller fish are removed easily. However, larger fish tend to struggle and need to be disentangled carefully to prevent damage to the nets.